Evaluation of home-mode ELISA system for thedetection of antibodies against Escherichia coli O157:H7 using purified lipopolysaccharide - Baghdad Science Journal (مجلة بغداد للعلوم)
An enzyme linked immunosorbent assay (ELISA) for the detection and quantitation of human immunoglobulin G (IgG) antibodies against vero- cytotoxine (VT) producing Escherichia coli serogroup O157:H7 was produced. E. coli O157: H7 lipopolysaccharide was extracted from locally isolated strains by using hot phenol- water method, followed by partial purification using gel filtration chromatography by sepharose- 4B. The purity of the lipopolysaccharide was checked by measuring the protein and nucleic acid content and then used as antigen. Four isolates of vero- cytotoxin producing E. coli serogroup O157:H7 was obtained by culturing 350 stool samples from children suffering from bloody diarrhea. These isolates were identified on bacteriological, serological and biochemical basis. Toxin production was confirmed on laboratory animals as well as by cytopathic effect on tissue culture. The possibility of using E. coli O157:H7 lipopolysaccharide in an enzyme- linked immunosorbent assay for the routine diagnostic testing of serum from patients for evidence of O157:H7 infection is discussed.